Evaluation of the management practices of small-scale dairy farmers in the North-Eastern Free State - Masiteng, Takisi Janki (Bloemfontein: Central University of Technology, Free State, 2000)
The study evaluated the management practices of small-scale dairy farmers in the NorthEastern Free State. The sampling area focused on small-scale dairy farmers in the former self-governing territory of Qwaqwa, as well as parts of the Harrismith, Kestell and Bethlehem districts where newly settled land-reform beneficiaries are concentrated A total mlmber of J J 4 farm units were established and 96 black farmers were settled by Agri-Eco. Small-scale dairy farming in the North-Eastern Free State is mostly practised by black farmers on communal and state land farms. In the new political dispensation, small-scale dairy farmers are still "disadvantaged'~ These farmers stnlggle to secure financial assistance from financing institutions due to vari01lS reasons such as a lack of land temlre or other assets for security reasons, a lack of reliable marketplaces, poor infrastnlcture, inadequate production programmes and production experience, (md a lack of technical know-how. The research found that most of the problems experienced by the farmers were related to the unresolved land tenure system (communal land), availability of water, working capital, veld buming, co-operation among farmers (farming group schemes) and extension services to advise small-scale dairy farmers. Regarding labour, all the small-scale dairy farmers in the sample made use of human labour due to a lack of the availability of mechanical implements. Regarding their future as small-scale dairy farmers and their aspirations and needs, farmers agreed that prerequisites f or success are: knowledge, skills, training and co-operation among themselves. The study showed that future interventions aimed at improving and strengthening the sustainability and the livelihoods of the small-scale dairy farmers, ensuring equity and redUCing economic vulllerability of small-scale dairy projects should take into account a Ilumber of different factors, which include the follOWing: (i) Government should endeavour to provide an effective extension service, establishing linkages with formal channels of marketing, local markets and informal marketing systems, training in farming principles, finanCial assistance, assistance in obtaining a farm or more land, improving environmenlal conservation and promoting social infrastnlcture. (ii) Other farmers and neighbours can play a major role in training, providing technical assistance to dairy farmers and providing advice 011 marketing. (iii) Participatory approaches are needed in addressing the problems and the needs of the smal/-scale dairy farmers, as they al/ow farmers to maintain ful/ authority over land, natural resources and water management and management decisiollS. The study reveals that mixed farming should be promoted, since it is unlikely that smal/-scale farmers can make a living purely from dairying.
Thesis
Keywords: Dairy farming - South Africa - North-Eastern Free State; Dairying - Management - South Africa - North-Eastern Free State; Dairy farmers